ANALISIS PENGARUH PROFITABILITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF YANG TERDAFTAR DI BEI - Hendrayani, Eka; Hurnis, Delfi; fitria, Fitria; putri, Anne; Sari, Rika Novita (Jurnal Ekonomi, 2021)
CSR is a Corporate moral responsibility towards the community. The company not only provides goods and services that are good for the community but also helps maintain environmental and physical quality by making a positive contribution to the welfare of the community. This study aims to determine the influence and magnitude of the effect of CSR Profitability and Disclosure on Automotive Manufacturing sub- sector companies on the the stock Exchange in 2016-2018 and to determine the effect of ROA, ROE, dan NPM on CSR Disclosure. The data collection method used is the documentation of financial statements issued by the company. The population in this study is the Automotive sub-sector companies listed on the Stock Exchange in 2016-2018. The analytical method used is multiple linear regression method. The results showed that profitability measured by ROA,ROE, dan NPM significantly influence CSR Disclosure.Keywords : CSR disclosures; NPM; ROA; ROECSR merupakan konsep atau tindakan rasa tanggung jawab perusahaan terhadap sosial atau lingkungan sekitar dimana perusahaan itu berada. Tujuan dari penelitian ini adalah untuk melihat seberapa besar  pengaruh  Profitabilitas dan Pengungkapan CSR pada perusahaan manufaktur Otomotif di BEI tahun 2016-2018. Metode pengumpulan data adalah dokumentasi laporan keuangan yang dikeluarkan perusahaan. Populasi adalah perusahaan manufaktur sub sektor Otomotif yang terdaftar di BEI tahun 2016-2018. Alat analisis yang digunakan adalah metode regresi linear berganda. Kata kunci : ROA, ROE, NPM dan Pengungkapan CSR. Kata kunci : NPM; Pengungkapan CSR; ROA; ROE